Evaluation the Level of Dieldrin and Heptachlor in Iraqi People - Jawad, Alaa H (Al-Nahrain Journal of Science, 2017)
Organochlorine pesticides for whatever length of time that been extensively utilized as a part of farming and in public health as highly effective pest control agents.They are lipophelic and have drawn out a half-existences of years to decades; thus, they amass in human fat tessues and a can bring about endless poisonous quality after long term exposure.To detect and measure the concentrations of organochlorine pesticides, (Dieldrin and Heptachlor) in serum and fatty tissue samples and studies their correlation with lipids in order to reveal the need. for human monitoring.The study was conducted on 50 samples of blood and fatty tissues to determine their lipid concentrations and detect metabolites of organochlorine pesticides and asses their1correlations using HPLC.The study observed that there were raised serum concentrations of lipids which were positively corresponded with lifted serum convergences of Dieldrin and Heptachlor pesticides.Mean serum concentrations of triglycerides was inside “normal” range while mean serum of aggregate cholesterol was hoisted above ordinary range. Rate of grouping of lipid to serum Dieldrin was higher than that of Heptachlor in living subjects.